2016
DOI: 10.1002/aenm.201600763
|View full text |Cite
|
Sign up to set email alerts
|

Watchband‐Like Supercapacitors with Body Temperature Inducible Shape Memory Ability

Abstract: shopping, detecting body-health, and so on. Nowadays, many major companies are working on exploring more functions on smart watches. In view of diverse functions of smart watches, there are increasing demands on their corresponding energy storage devices with high energy and/or power supply ability. [9][10][11][12][13] However, the energy storage devices are commonly placed in the watches with very small volume, which seriously limit their current energy storage ability and the future boost space. As we know, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 58 publications
0
81
1
Order By: Relevance
“…It is noted that, the indirect energy sources such as wind energy, solar energy and tidal energy are very promising to meet the requirements of people's daily life, but they are different greatly in geography and even change over time. So it is extremely important to develop advanced sustainable energy storage devices [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that, the indirect energy sources such as wind energy, solar energy and tidal energy are very promising to meet the requirements of people's daily life, but they are different greatly in geography and even change over time. So it is extremely important to develop advanced sustainable energy storage devices [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [109] Copyright 2016, Wiley. c) CV curves of the SMSCs before and after shape restoration.…”
Section: Resultsmentioning
confidence: 99%
“…Yan et al reported a smart design for a watchband-like supercapacitor based on a TiNi alloy, with a shape memory ability inducible by body temperature (Figure 6a). [109] The shape-memory TiNi alloy is renowned to its outstanding flexibility, stability and biocompatibility, and its shape restoration is driven by the reversible crystalline phase transformation between martensite and austenite triggered by heat. For device assembly, reduced graphene oxide (rGO) coated on TiNi alloy (TNA) flake was used as the negative electrode, while MnO 2 deposited on ultrathin Ni foil served as the positive electrode.…”
Section: Shape-memory Ability In Response To External Mechanical Defomentioning
confidence: 99%
“…e,f) Reproduced with permission. [172] The asymmetric supercapacitor consisted of reduced graphene oxide on a shapememory TiNi foil as negative electrode and MnO 2 onto a Ni film as positive electrode, showing stable performance under static bending at different angles and dynamic shape-memory restoration bending (Figure 19e). g-i) Reproduced with permission.…”
Section: Restorable and Degradable Supercapacitorsmentioning
confidence: 99%
“…In these cases, the shape restoration is not appropriate to repair failures. [172] Copyright 2016, John Wiley and Sons. Thanks to healable materials, a self-healing symmetric supercapacitor has been achieved by using healable materials as substrates to disperse Figure 19.…”
Section: Restorable and Degradable Supercapacitorsmentioning
confidence: 99%